European guidelines for quality assurance in colorectal cancer screening and diagnosis: Overview and introduction to the full Supplement publication - Von Karsa, L.; Patnick, J.; Segnan, N.; Atkin, W.; Halloran, S.; Lansdorp_Vogelaar, Iris; Malila, N.; Minozzi, S.; Moss, S.; Quirke, P.; Steele, R.; Vieth, M.; et al. (2013)
Population-based screening for early detection and treatment of colorectal cancer (CRC) and precursor lesions, using evidence-based methods, can be effective in populations with a significant burden of the disease provided the services are of high quality. Multidisciplinary, evidence-based guidelines for quality assurance in CRC screening and diagnosis have been developed by experts in a project co-financed by the European Union. The 450-page guidelines were published in book format by the European Commission in 2010.They include 10 chapters and over 250 recommendations, individually graded according to the strength of the recommendation and the supporting evidence. Adoption of the recommendations can improve and maintain the quality and effectiveness of an entire screening process, including identification and invitation of the target population, diagnosis and management of the disease and appropriate surveillance in people with detected lesions. To make the principles, recommendations and standards in the guidelines known to a wider professional and scientific community and to facilitate their use in the scientific literature, the original content is presented in journal format in an open-access Supplement of Endoscopy. The editors have prepared the present overview to inform readers of the comprehensive scope and content of the guidelines. © Georg Thieme Verlag KG Stuttgart · New York.